Analisis Manajemen Risiko Aplikasi E-Rapor Menggunakan COBIT 4.1 Domain P09 - Melina Manurung; Resad Setyadi (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
The E-Report application is a system to make it easier for teachers, staff, students, parents, and the Ministry of Education and Culture to find out the results of student learning analysis of SMA N 1 Laguboti applying the E-Report application as a means of communication between schools, students and parents. The problem with E-Report in SMA N 1 Laguboti is that there is an error when using the application to input data. The purpose of this study was to analyze risk management in the E-Report application at SMA N 1 Laguboti. This research method uses quantitative methods. The measuring instrument method for analyzing the sample questionnaire questions uses the Control Objective for Information and Related Technology (COBIT 4.1) domain Plan and Organize (PO9). COBIT 4.1. The method of data collection in this research is the distribution of questionnaires to obtain data that will be SPSS. COBIT 4.1 analysis is a framework for analyzing and ensuring the alignment of information technology with business management by calculating the maturity level. The results of this study are the value of the maturity level of risk management for the E-Report application at SMA N 1 Laguboti of 2,51087267 is Defined Process. The recommendation from this research is that there is a need for a special person to control the E-Report application at SMA N 1 Laguboti and provide training on the use of the E-Report application.